The first Lithuanian book of problems in arithmetic - Rumšas , P. (Psichologija, 1972)
The beginnings of teaching arithmetic in the Lithuanian language can be found in the primers of the 18th - 19th centuries. In the first half of the l9th century the first three manuals of arithmetic were written but remained unpublished. The book of problems in arithmetic [14] is the first book published in Lithuanian; it was written in 1879 and for some time was being copied by hand and distributed. The manuscript of this book is preserved at the Library of the Academy of Sciences of Lithuania. Before publication the book of problems was fundamentally remade and supplemented. The three sections about abstract, concrete and fractional numbers comprise 630 problems, most of them textual. Some problems are recommended to be solved with the help of equations. The arithmetical glossary is of great value. Here with the help of Polish and German terms the meanings of the words are explained.